The impact of birth order on behavior in contact team sports: Evidence of rugby teams - Delbianco, Fernando Andrés (2020)
Several studies have shown that birth order and the sex of siblings may have an influence on individual behavioral traits. In particular, it has been found that second brothers (of older male siblings) tend to have more disciplinary problems. If this is the case, this should also be shown in contact sports. To assess this hypothesis, we use a data set from the South Rugby Union from the region of Bahía Blanca, Argentina, and information obtained by surveying more than 400 players of that league. We find a statistically significant positive relation between being a second-born male rugby player with an older male brother and the number of yellow cards received.